Poverty Reduction Support Credits : An Evaluation of World Bank Support - Independent Evaluation Group (Washington, DC: World Bank, 2012)
The goal of Poverty Reduction Support Credits (PRSCs), introduced in early 2001 under World Bank Interim guidelines, was to help countries implement comprehensive, country-owned development strategies to promote growth, improve social conditions, and reduce poverty. PRSCs were intended to ease conditionality and to make annual flows to recipient countries predictable and integrated with their budgets. To reduce fiduciary risks associated with budget support, PRSCs were intended to strengthen domestic budget processes. They were seen as providing a framework for donor harmonization and were meant to focus on achieving clearly defined results.